Starfishes of the Philippine seas and adjacent waters - Fisher, Walter K. (Washington Govt. print off., 1919)
At head of title: ... Contributions to the biology of the Philippine archipelago and adjacent regions.On verso of t.-p.: Bulletin of the United States National museum.Plates printed on both sides.Report based upon a collection made by the United States Fisheries steamer Albatross, 1907-1910, in the region of the Philippine islands, Colebes and Molucca islands.Bibliography: p. 541-546.
Keywords: Echinodermata; Echinodermata; Starfishes